Evaluation of Perceived Acceptability, Beauty and Value of Different Orthodontic Brackets - Moshkelgosha V; Salahi M; Rostami Sh (Shiraz University of Medical Sciences, 2015)
Statement of Problem: Although different types of aesthetic brackets are introduced to orthodontic profession to reduce the complaints about the metallic braces, little studies have been done to assess patient's views regarding the attractiveness and acceptance of such brackets. Objectives: The goal of this study was to evaluate the perceived acceptability, beauty and value of different orthodontic brackets. Materials and Methods: In a cross-sectional study, three groups of subjects consisting of dental school clinic patients, specialty clinic patients, and art students were interviewed. Sample size was decided 116 in each group. The photographic images of six types of brackets which were placed in an adult mouth were shown to the subjects and they were asked to answer the questions that evaluate attractiveness by visual analog scale (VAS), acceptability of different brackets, and willingness to pay (WTP) for an aesthetic bracket in comparison to a regular bracket. Reliability was measured by giving questionnaires to 20 respondents by a two-week interval. VAS rating was compared by ANOVA. Mann U Whitney and Chi-square tests were used to compare the acceptability between groups when necessary. Results: The reliability measurement results performed by ICC were 0.86 for attractiveness, 0.6 for acceptability, and 0.93 for WTP questions. Lingual brackets had the highest attractiveness rating while metal brackets were considered the lowest aesthetic appliance by all groups of the study. The acceptability of ceramic bracket was highest in all groups. While most appliances evaluated had average acceptability, the large metallic brackets were rated very low. WTP for aesthetic braces was higher in art students than other groups. Conclusions: Lingual brackets were the most attractive but had very low acceptability rate. Small metal brackets had a good acceptability rate. Large metal brackets were the least attractive and had the lowest acceptability. Parents accepted aesthetic brackets for their children even when it cost more.